Health literacy studies conducted in Australia: a scoping review - Riaz, Fahad; Long, Chiau Ming; Munawar, Khadeeja; Razi Zaidi, Syed Tabish; Patel, Rahul P.; Khan, Tahir Mehmood; Elmer, Shandell (MDPI, 2019)
Health literacy (HL) is an essential component of various literacies mentioned in the ﬁeld of health and education, including cultural, technological, media and scientiﬁc literacies. It is important for motivating higher consumer engagement. We aimed to review previous studies of HL in Australia to inform future studies, extend current knowledge and further enhance HL. Using search strings, a systematic search of four databases (i.e., MEDLINE; Embase; CINAHL and Eric) was carried out. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) based search strategy led to identiﬁcation of a total of N = 9696 records, that were further screened for inclusion in the review. The review ﬁndings were categorized into three major themes: (1) HL and health numeracy; (2) contrast of: knowledge deﬁciency, knowledge gained, problems of current health care system and (3) HL measurement methods and its domains. The ﬁndings from this scoping review show a dearth of measurement tools with sound psychometric properties for assessing HL. The ﬁndings also reveal low levels of HL in consumers which is in turn affecting health-related behaviors, utilization of health services and navigation of the health system. More recent developments have tried to integrate vital aspects, including introduction of applications to increase HL and exploring HL in Aboriginal communities.